Política industrial e desenvolvimento: o papel do BNDES no desenvolvimento industrial brasileiro - Cano, Isaias Pinto Lima (Universidade Federal de São Carlos, 2014)
This work uses a historical-institutional and theoretical developmental approach to the analysis of the transformations of different forms of activity of the Banco Nacional para o Desenvolvimento Econômico e Social (BNDES) as an instrument of industrial and economic policy from the 1950 s, with focus between 2003 and 2012. Thus, this work discusses the transformations of the form of action off the bench in three major qualitatively distinct blocks: (i) height and crisis of national developmentalism, (ii) the liberal reaction and (iii) the new developmentalism that flourished in the years after 2002.
Industrial policy and developmentalism: the Role of BNDES in the Brazilian Industrial Development.
Keywords: política industrial - Brasil; industrialização; Banco Nacional de Desenvolvimento Econômico e Social (Brasil); política industrial e desenvolvimentismo; banco de investimento; atuação do BNDES.; industrial policy and developmentalism; investment bank. BNDES performance; CIENCIAS SOCIAIS APLICADAS::ECONOMIA